Complex reprocessing of industrial alkaline waste of alumina production (red mud) for solving raw materials and environmental problems - Boyarintsev Alexander (E3S Web of Conferences, 2021)
Red mud are industrial large-scale toxic wastes of bauxite ore processing according to the Bayer method. They contain macrocomponents such as iron, aluminum, calcium, silicon, as well as a number of the most valuable and critical metals (microcomponents): scandium, gallium, germanium and rare earth elements (REEs), which are used in modern high-tech industry. Due to the relatively high content of scandium and REEs, red mud can be considered as a promising secondary source. Significant amounts of accumulated red mud and new flows of this waste entering the slime storage facilities need to be processed to obtaine the required valuable products. Development of complex reprocessing approach play an important role in addressing the problem of the elimination of red mud as toxic waste. Within the framework of this subject, the report considers the concept of complex reprocessing of Bogoslovsky Aluminum Plant (Russia) red mud, which includes the extraction of aluminum, scandium, REEs, zirconium and the production of iron-containing concentrate for ferrous metallurgy. The use of low-aggressive carbonate media and carbonation method using carbon dioxide gas characterizes this approach as more environmentally and technologically safe. The development of effective technology for utilization of red mud will not only provide a source of critical raw materials, but also solve the global environmental problem.